Směřování ke kvalitě 2016-2020 v pedagogicko-psychologické přípravě budoucích učitelů na PdF MU - Kratochvílová, Jana (Masaryk University Press, 2020)
Title in English: Towards the quality 2016-2020 in pedagogical-psychological preparation of future teachers at the Faculty of Education MU. The aim of this publication is to introduce the Department of Education of the Faculty of Education, Masaryk University and its results of evaluation at the end of the three-year implementation period of the newly accredited pedagogical-psychological module of teacher education. The publication presents the mission and vision of the workplace, its planned curriculum, theoretical foundations and achievements in research, creative and project areas. The main part is formed by the evaluation of the practical implementation of the new curriculum in practice.